Microbiome analysis of feline odontoclastic resorptive lesion (FORL) and feline oral health. Issue 4 (15th April 2021) - Thomas, Sheeba; Lappin, David F.; Nile, Christopher J.; Spears, Julie; Bennett, David; Brandt, Bernd W.; Riggio, Marcello P.
Abstract : Introduction. Feline odontoclastic resorptive lesion (FORL) is one of the most common and painful oral diseases of the cat. It is characterised by tooth resorption due to destructive activity of odontoclasts. FORL can result in tooth loss. While the aetiology of FORL is not clearly understood, it is thought to be multifactorial and bacteria are likely to play a major role. Hypothesis. Dysbiosis of the normal feline oral microbiota leads to an alteration in commensal bacteria populations, which results in the development of FORL. Aim. The purpose of the current study was to determine the composition of the microbiomes associated with feline oral health and FORL. Methodology. Supragingival plaque was collected from 25 cats with a healthy oral cavity and 40 cats with FORL. DNA was extracted from each sample, the V4 region of the 16S rRNA gene amplified by polymerase chain reaction and amplicons sequenced. Diversity and species richness analyses were performed, principal component analysis was used to explore differences between the oral microbiomes of healthy cats and those with FORL, and linear discriminant analysis effect size was used to assess differences between the groups. Results. The six most abundant bacterial genera identified were Bergeyella, Capnocytophaga, Lampropedia, Morexella, Porphyromonas and Treponema . Two-step cluster analysis of the data identified two FORL sub-groups (FORL-1, FORL-2). The FORL-2 sub-group was very similar to the healthy group, whilst the FORL-1 sub-group was clearly different from both the FORL-2 sub-group and the healthy groups. In this analysis, Capnocytophaga ( P <0.001) and Lampropedia ( P <0.01) were found at significantly lower levels and Porphyromonas at a slightly higher level in the FORL-1 sub-group compared to the healthy and FORL-2 sub-groups. Microbial diversity was found to be less in the FORL-1 sub-group than in the healthy group. Lampropedia sp., a phosphate-accumulating oral commensal species, was significantly lower in the FORL-1 sub-group. Conclusion. The oral microbiota associated with the FORL-1 sub-group is distinct from that found in the healthy group and FORL-2 sub-group. Lampropedia species may influence the local calcium-phosphate ratio, which could be a factor in tooth and bone resorption observed in FORL.